2023
DOI: 10.1002/adfm.202214658
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Ni/N/C Single‐Site Catalyst Achieving Industrial‐Level Current Density and Ultra‐Wide Potential Plateau of High CO Faradic Efficiency for CO2 Electroreduction

Abstract: The practical applications of CO 2 electroreduction to CO driven by renewable electricity should simultaneously meet the requests of industrial-level CO partial current density (J CO ) at least 100 mA cm −2 , wide potential window of high CO faradic efficiency (FE CO ), and low cost. Herein, a new strategy is reported to construct porous hierarchical Ni/N/C single-site catalyst with excellent catalytic activity via coating Ni-containing ZIF-8 on mesostructured basic magnesium carbonate template followed by pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Notably, we calculated the TOF (calculation details in the Experimental Section) under different potentials. As shown in Figure d, the TOF of HP-Ni-NC-2 reaches 3003 h –1 at −0.9 V (vs RHE), which is comparable to that of some reported catalysts for CO 2 electrochemical reduction to CO. ,,, …”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Notably, we calculated the TOF (calculation details in the Experimental Section) under different potentials. As shown in Figure d, the TOF of HP-Ni-NC-2 reaches 3003 h –1 at −0.9 V (vs RHE), which is comparable to that of some reported catalysts for CO 2 electrochemical reduction to CO. ,,, …”
Section: Resultssupporting
confidence: 77%
“…The chemical states and surface compositions of all catalysts were analyzed by XPS. As shown in Figure c, the Ni 2p spectrum of HP-Ni-NC-2 displays two peaks at 855.7 eV (2p 3/2 ) and 872.8 eV (2p 1/2 ), which are negative compared to the binding energy of Ni 2+ but positive compared to that of Ni 0 , indicative of the existence of the oxidation state of Ni δ+ (0 < δ < 2) in HP-Ni-NC-2 catalyst. , The chemical states of Ni species in HP-Ni-NC-4 and Ni-NC-2 are similar to that in HP-Ni-NC-2 (Figures S9 and S10). The N 1s spectra of all catalysts are presented in Figures d and S11–S13.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…32,33 Moreover, our recent reports have shown that constructing porous hierarchical catalysts can facilitate the charge/mass transfer kinetics to boost the expression of electrocatalytic activity. 34,35 Herein, by DFT optimization of metal species in M−N−C catalysts, the edge-hosted NiN…”
mentioning
confidence: 99%
“…To achieve the industrial-level current density, the metal active sites should be first optimized to possess the best intrinsic activity of the CO 2 RR to CO or HER, and on the other side, the catalyst structure should be designed to facilitate charge/mass synergic transfer for fully expressing the catalytic activity. As is known, density functional theory (DFT) is a powerful tool to search the active MN x moieties to electrocatalytic reactions with suitable descriptors, which could be adopted to optimize the active species for syngas production. , Moreover, our recent reports have shown that constructing porous hierarchical catalysts can facilitate the charge/mass transfer kinetics to boost the expression of electrocatalytic activity. , Herein, by DFT optimization of metal species in M–N–C catalysts, the edge-hosted NiN 4 and CoN 4 configurations with the respective most-active CO 2 RR to CO and HER performances are screened out to construct the electrocatalysts for syngas production. The corresponding hierarchical Co x Ni 1– x –N–C DSAC with coexisting isolated CoN 4 and NiN 4 moieties was constructed by a two-step pyrolysis based on the mesostructured basic magnesium carbonate (m-MgCO 3 ·Mg­(OH) 2 ) templating method .…”
mentioning
confidence: 99%